15 Cardiac implantable electronic device complications in a real-world setting. (16th October 2019) - Quinn, S; Elhadi, M; Weedle, R; Nolan, P; Keane, S; Murphy, T; Hynes, B; Smyth, Y; MacNeill, B; Crowley, J; Nash, P
Abstract : Introduction: Cardiac implantable electronic devices (CIED) are associated with low rates of procedure-related complications but many of these complications are associated with significant morbidity and prolonged hospitalisations. The aim of this study was to perform a retrospective 'real world' review of CIED complication rates in a tertiary centre in the West of Ireland and compare rates to a multi-centre CIED complication registry, the REPLACE registry 1 . Methods: All patients who received a new device implant (ICD, PPM, CRT) or revision of an existing implant from 01/01/2016 to 31/12/2016 at Galway University Hospital were included (table 1). Data on complications associated with the procedure were collected from patient records including electronic discharge summaries, cardiothoracic surgery records, catheterisation laboratory log book records, patient clinical files and the pacing registry G-Pace. Complication rates were compared to the REPLACE registry 1 data using the same major and minor complication criteria (table 2). Results: 373 patients were included in the analysis (male = 257 (69%), female = 116 (31%)) and were followed up for an average of 28.6±7.9 months. The mean age was 73±13 years at the time of the procedure. 106 (28%) patients were transfers from peripheral hospitals and 76 (20%) of these patients returned to their referring centre on the same day. 156 (42%) patients were electively admissions, the remaining 111 (30%) patients were acutely admitted. 73 patients developed (19.6%) complications in the follow up period. Of these, 30 (8%) were early (i.e. before discharge, range 0–4 days) and the remaining 43 (11.5%, ) occurred post-discharge. 12 (3%) occurred at 0–1 months, 9 (2%) at 1–3 months, 13 (3%) at 3- 12 months, and 9 (2%) >12 months. The complications with the highest rates (>1%) included lead revision (n=23, 8.6%), pneumothorax (n=8, 4.8%), device infection (n=9, 2.4%) and haematoma/swelling (all n=9, 2.4%). One patient (0.3%) died from RV perforation. Conclusion: Overall the CIED major complication rate at our centre is comparable to that of the REPLACE registry 1 . Major complications such as lead revisions, pneumothorax, infection and haematoma were numerically higher when compared to the same study. Our findings illustrate the risk and variety of complications that can occur with these procedures and highlights the need ongoing strategies to minimise the risks of these complications.